Nerve growth factor protects retinal ganglion cells against injury induced by retinal ischemia–reperfusion in rats. (April 2015) - Chen, Qian; Wang, Haitao; Liao, Sufen; Gao, Yang; Liao, Rifang; Little, Peter J.; Xu, Jiangping; Feng, Zhong-Ping; Zheng, Yongxin; Zheng, Wenhua
Abstract In this study, we investigated the protective effect of mouse nerve growth factor (NGF) on retinal ganglion cell (RGC) injury induced by retinal ischemia–reperfusion (RIR) in rats and explored its possible mechanisms of action. RIR caused a significant injury to RGCs and an obvious impairment of the inner retina functions, which could be seen from flash electroretinogram and flash visual evoked potential recordings. RIR also increased the expression of the apoptotic protein Bax while decreasing the expression of Bcl-2 and the phosphorylation of protein kinase B (Akt) in RGCs. Preinjection (i.m.) of NGF for 22 d reversed the injury induced by RIR and ameliorated the inner retina functions. NGF also reduced the expression of Bax and reversed the reduction of Bcl-2 and the phosphorylated Akt induced by RIR. These results indicate that NGF produces a neuroprotective effect on RGCs against RIR injury and the protective effect of NGF is mainly mediated by the PI-3K/Akt signaling pathway.